RELATIONSHIP GUIDANCE/ENRICHMENT OF INDONESIAN COMPETENCY EXAM (UKNI) WITH GRADUATION OF STUDENTS IN THE INDONESIAN NERS COMPETENCY TEST IN SOUTH SULAWESI - ahmad musawir (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
Objectives: Indonesian Competency Exam (UKNI) is a process of measuring skills knowledge, and performance of students in universities that obtaining nursing department which aimed to achieve the competency standards of alumnae who meet up with work proficiency standard. Unfortunately 24 nursing department/institution in South Sulawesi that conduct UKNI have passing rates only reached 21.19% in four periods of UKNI completion, these results lower than the national UKNI results which reached 37%. Methods: The design of the research is a cross sectional study which discusses and analyzes the relationship between UKNI guidance / enrichment with the graduation level of students at UKNI, 95 lecturers in 18 nursing study programs in South Sulawesi who were given a questionnaire. Results: The results were tested using the chi square correlation test with a significance level of p-value = 0.05. The results showed that there was a relationship between the guidance / enrichment of UKNI (p = 0.00) with the graduation level of students in the nurses' competency test. These results indicate the better the implementation of guidance / enrichment of UKNI by the study program, the better the graduation rate of students in UKNI. Conclusion: The role of institutions in conducting UKNI guidance / enrichment is very closely related to the graduation level of students in competency tests. Further research needs to be carried out to analyze more specifically the form of debriefing carried out by institutions that influence differences in the graduation level of students in each study program in UKNI.